2020
DOI: 10.3390/cells9061465
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Three-Dimensional DNA Fluorescent In Situ Hybridization (3D DNA FISH) for the Detection of Anaplastic Lymphoma Kinase (ALK) in Non-Small Cell Lung Cancer (NSCLC) Circulating Tumor Cells

Abstract: Tumor tissue biopsy is often limited for non-small cell lung cancer (NSCLC) patients and alternative sources of tumoral information are desirable to determine molecular alterations such as anaplastic lymphoma kinase (ALK) rearrangements. Circulating tumor cells (CTCs) are an appealing component of liquid biopsies, which can be sampled serially over the course of treatment. In this study, we enrolled a cohort of ALK-positive (n = 8) and ALK-negative (n = 12) NSCLC patients, enriched for CTCs using spiral microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The enumeration and characterization of CTCs provided a minimally invasive and, therefore, repeatable, method despite being present in extremely low numbers, enabling the sampling of tumor cells from peripheral blood and monitoring PD-L1 expression on tumor cells over time. In addition, EML4-ALK rearrangements have been reported to be found in CTCs [ 56 ]. Thus, combining CTC and peripheral immune subset analyses may make it possible to longitudinally evaluate serial human specimens during treatment (at pre-treatment, early-on-treatment, and progression time points), which allow for deep analysis to unveil potential mechanisms of therapeutic resistance [ 16 , 50 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enumeration and characterization of CTCs provided a minimally invasive and, therefore, repeatable, method despite being present in extremely low numbers, enabling the sampling of tumor cells from peripheral blood and monitoring PD-L1 expression on tumor cells over time. In addition, EML4-ALK rearrangements have been reported to be found in CTCs [ 56 ]. Thus, combining CTC and peripheral immune subset analyses may make it possible to longitudinally evaluate serial human specimens during treatment (at pre-treatment, early-on-treatment, and progression time points), which allow for deep analysis to unveil potential mechanisms of therapeutic resistance [ 16 , 50 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization of CTCs has revealed that genomic changes of the tumor can be readily assessed via CTCs. This was recently highlighted by a number of studies identifying translocations/mutations in anaplastic lymphoma kinase (ALK) and EGFR in CTCs [ 74 , 75 , 76 , 77 , 78 ]. For EGFR mutations, the sensitivity of the assay increased with higher numbers of detected CTCs with concordance between EGFR mutation status in the tumor and CTC samples [ 77 ].…”
Section: Evolving Role Of Liquid Biopsy In Nsclcmentioning
confidence: 99%
“…In clinical practice, CTCs represent a real-time, minimally invasive alternative source of tumor material. CTCs can be used to assess the landscape of primary and metastatic tumor in the body over time by sampling the blood serially over the course of treatment [ 147 ]. CTCs information can be used to monitor disease progression and to predict treatment response.…”
Section: Ctcs Information In Clinical Practicementioning
confidence: 99%
“…CTCs information can be used to monitor disease progression and to predict treatment response. The analysis of CTCs can also be used to select patients for targeted therapies [ 77 , 147 ].…”
Section: Ctcs Information In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation